Nutritional value of millets - Malathi, V M; Venkateswarlu, R; Jacob, Jinu; Ratnavathi, C V (Indian Farming, 2023)
Millets include a group of small-grained cereals widely cultivated and consumed throughout arid and semi-arid parts of the world. They are agronomically superior in terms of shorter growing periods, have ability to grow in marginal lands with minimum inputs and are resistant to biotic and abiotic stresses. More importantly, the millet grains are nutritious with a carbohydrate content of about 60–68%, protein content of 6–12%, fat content of 1.7–5.4% and total ash content of about 1.3–2.7%. They are good sources of dietary fibre and micronutrients including minerals and B-vitamins. Apart from this, millets contain phytochemicals including the phenolic compounds with excellent health beneficial attributes. Owing to their excellent nutritional value and the ability to survive under changing climate scenarios, these crops may serve vital role in achieving global nutritional security in a sustainable manner.